Elevated Serum Growth Differentiation Factor 15 Levels as a Potential Biomarker of the Efficacy of Imeglimin in Individuals With Type 2 Diabetes Mellitus: An Exploratory Study - Wada, Naoki; Murakami, Takaaki; Fauzi, Muhammad; Sakaki, Kentaro; Oshima, Shinobu; Shimada, Yoshihito; Asai, Kanae; Oshima, Ayako; Nomura, Satoko; Joo, Erina; Mori, Michiko; Fujiwara, Ryoko; et al. (Journal of clinical medicine research, 2024)
The aim of the present study was to conduct a prospective observational study to explore the effects of imeglimin on systemic energy metabolism/body composition and to identify potential mitochondria-related biomarkers of the efficacy of the drug in clinical settings. In this prospective observational study, 16 participants with type 2 diabetes mellitus in the diabetes clinic of Kyoto University Hospital were enrolled. Individuals were started on imeglimin as monotherapy or add-on therapy. After 3 months under imeglimin treatment, there was no significant change in basal metabolism or body composition. However, serum levels of growth differentiation factor 15 (GDF15) were higher while those of serum fibroblast growth factor 21 and urine 8-hydroxy-2'-deoxyguanosine were not changed. Additional examination revealed that imeglimin induces GDF15 protein release from human hepatocytes. Three-month imeglimin treatment increased serum GDF15 levels in clinical type 2 diabetes mellitus patients along with little change in basal metabolism or body composition, suggesting GDF15 as a potential marker for the efficacy of imeglimin.